Travelling as a Subject - Dickel, Mirka (Journal of Geography Education, 2007)
Pupils are usually highly motivated before class trips. Though, sight-seeing very often reduces pupils’ motivation to a minimum. This dilemma has been faced from different angles and subjects. Alternative suggestions and ideas hint at modified designs of the trips’ integration in classes. They are obliged to different teaching traditions, emphasize various aspects of teaching and learning, focus on distinct educational aims and target groups. Shifts of paradigm have already been spotted. However, a compound, revised, up-to-date theoretical outline as a fundamentum for an estimation and discussion of recent approaches has been missing so far and is the thesis’ matter of concern. As the paper bases methodologically on "narration" opposite attitudes towards the educational value of school trips have been taken into account. Due to frictions and fractions between these positions epistemological questions become apparent. They point at a constructive teaching and learning conception which can generally speaking be characterized in terms of openness, reflection and process-orientation.